Polarization independent and tunable plasmon induced transparency for slow light - Yang, Hanning; Owiti, Edgar; Pei, Yanbo; Li, Siren; Liu, Peng; Sun, Xiudong (Royal Society of Chemistry, 2017)
A novel metamaterial composed of a Ag nanoprism periodic tetramer is proposed in this paper. The metamaterial has high structural symmetry and shows polarization independent plasmon-induced transparency (PIT), demonstrated through simulation based on a finite element method. Resonant wavelength and transmissivity of the transparency window is flexibly tuned by changing the fillet radius, the edge length, and the thickness of the Ag nanoprisms. A slow-light effect, caused by an adjustable PIT with a special line shape, can also be flexibly manipulated as the nanoprisms are filleted. The maximum group index value of the metamaterial ranges from 71 to 225. The effects show potential for application in novel plasmonic environmental sensors and slow-light devices